Audiovisions - Siegfried Zielinski (Amsterdam University Press, 2014)
The innovation of cinematography in the last decade of the nineteenth century was the expression and media vanishing point of technical, cultural, and social processes that are generally referred to as industrialisation. In the rhythmic projection of photographs arranged on perforated celluloid strips that outwitted human visual perception, in the anonymity of publicly accessible spaces vested with a highly intimate ambience, the human subjects who had been through industrialisation apparently discovered their appropriate and adequate communicative satisfaction. Reproducible dream worlds, staged for the eye and the ear, provided these subjects who had been rushed through the century of the steam engine, mechanisation, railways, and, lastly, electricity, with the material for satisfying their desires for rich sensory impressions, variety, diversions, escapism, but also for orientation. Yet even before the first noisy and flickering celluloid projectors began to run, before cinema was actually institutionalised, theoretical work was already in progress to supersede this stage of achievement in audiovisual events - although, obviously, not at first with this express purpose in mind. Twenty years before the first cinematographic shows in Paris, Berlin, London and New York, models for 'seeing machines'! were designed, models for a medium where the production of visual reproductions and their reception would almost coincide in time even though transmitter and receiver were spatially far apart. Telegraphy and telephony, respectively, were the models with regard to the positioning of the users of this communications teclmology. They were to be owners of their own equipment.